The Greek translation and validation of the electronic version of the Meno-D rating scale for post-menopausal depression. (15th April 2022) - Papazisis, Georgios; Tsakiridis, Ιoannis; Apostolopoulou, Aikaterini; Papaefstathiou, Efstathios; Bellali, Thalia; Liozidou, Athanasia; Pappa, Athanasia; Ainatzoglou, Alexandra; Tzitiridou, Maria; Billis, Antonis; Dagklis, Themistoklis
Menopausal transition and post-menopause constitute windows of increased vulnerability to depression. Recently, the Meno-D was introduced, a novel 12-item, with five distinct subscales. The aim of our study was to translate and validate the electronic version of the Meno-D among Greek post-menopausal women. Translation and back-translation were performed by an expert group, while face validity was assessed by five experts. Along with the Beck Depression Inventory-II, the Meno-D scale was distributed online to 502 post-menopausal women. A confirmatory factor analysis was performed to investigate construct validity and both convergent and discriminant validity were evaluated. The data analysis was performed using Statistical Package for Social Sciences and AMOS. The 5-factor model of Meno-D achieved adequate levels of goodness-of-fit indices, scoring lower values in discriminant validity examined with heterotrait-monotrait ratio and composite reliability. The significant correlation with the Beck Depression Inventory-ΙΙ revealed for all subscales was indicative of good convergent validity. An exploratory factor analysis was additionally performed, suggesting a 12-item tool comprising two subscales: (i) psychological and (ii) biological and achieving good levels of fit. Our data confirmed that the electronic version of Meno-D is a valid tool that can be used for screening and evaluation of depression in Greek post-menopausal women.